PENGEMBANGAN MEDIA INTERAKTIF BERBASIS E-MODUL GUNA MENUMBUHKAN MINAT BACA SISWA PADA MATA PELAJARAN PPKN MATERI KERAGAMAN BUDAYA SENI TARI DI JAWA BARAT KELAS IV SEKOLAH DASAR - Sobrina Salsabila Sobrina; Fitriyani (Amal Insani Foundation, 2023)
This study aims to produce E-Module learning media and test the feasibility of E-Module learning media to foster students' interest in reading. This research belongs to the Research and Development (RnD) type of research which adheres to the Borg and Gall development model in Sugiyono's book using 7 steps, namely: 1) data collection; 2) Product design; 3) product design; 4) design validation; 5) design revisions; 6) user feasibility test; 7) final product. The subjects of this study were fourth grade students at SDIT As Salam with data collection techniques using interviews, the respondents in this study were material, language and material experts as well as media users namely class teachers and students. The results of this study indicate that: (1) the E-Module learning media is declared feasible by material with a percentage of 80% material feasibility assessment including very feasible criteria, 100% language proficiency assessment with very feasible criteria and 92% media eligibility; (2) E-Module learning media is stated to be very effective by users, namely class teachers with a percentage of 87.5% and students 83.3%.